Restoring the shattered self a Christian counselor's guide to complex trauma - Davediuk Gingrich, Heather 1958- (IVP Academic, An imprint of InterVarsity Press, 2013)
Heather Gingrich brings years of counseling experience to bear on this delicate and difficult issue. She ably integrates the established research on trauma therapy with keen insights from her own experience and an intimate understanding of the special concerns related to Christian counseling--including a discussion of prayer and spiritual warfare. This book is a much-needed guide for working with complex trauma that is essential reading for counselors and pastors alike. --Back Cover